2012
DOI: 10.1097/meg.0b013e32834d09b9
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year serological follow-up of celiac disease in an Estonian population

Abstract: In a 10-year follow-up period, no new cases of CD were found in this Estonian population of school-children and young adults. Therefore, we presume no increase in CD during the last decade among this age group in Estonia. Additional studies are needed to determine whether similar results would be obtained in other age groups, because of differences in the CD prevalence between Estonian and other European populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The present study is the first on celiac disease epidemiology in Latvia, one of the three Baltic countries in Northeastern Europe where considerable political and socioeconomic changes have taken place over the last century. A previous study conducted in schoolchildren from Estonia, another Baltic country, revealed a 0.34% prevalence of celiac disease 33, 34 . In Polish children the prevalence of confirmed celiac disease is 0.25%, but the prevalence of positive serology is 0.8% 35…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The present study is the first on celiac disease epidemiology in Latvia, one of the three Baltic countries in Northeastern Europe where considerable political and socioeconomic changes have taken place over the last century. A previous study conducted in schoolchildren from Estonia, another Baltic country, revealed a 0.34% prevalence of celiac disease 33, 34 . In Polish children the prevalence of confirmed celiac disease is 0.25%, but the prevalence of positive serology is 0.8% 35…”
Section: Discussionmentioning
confidence: 92%
“…A previous study conducted in schoolchildren from Estonia, another Baltic country, revealed a 0.34% prevalence of celiac disease. 33,34 In Polish children the prevalence of confirmed celiac disease is 0.25%, but the prevalence of positive serology is 0.8%. 35 Prevalence figures in epidemiological studies are substantially influenced by the criteria set for diagnosing celiac disease.…”
Section: 32mentioning
confidence: 99%
“…Second, the two groups were recruited 10 years apart, although both groups were screened using IgA‐anti‐TG2 with exactly the same method. In addition, we followed up the population studied and rescreened them with IgA‐anti‐TG2 10 years after initial recruitment without finding any new cases of CD . Therefore we consider these two groups comparable and report a four times greater risk for developing CD (odds ratio [OR] 4.18, 95% CI 1.12, 15.64) in children with AD as in the general pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…However, population-representative screening further revealed that several countries, such as Argentina (135), Finland (113), Hungary (142, 143), Italy (121, 147149), Spain (154), Sweden (157160), and Turkey (163), were approaching a childhood prevalence of 1% or more. Meanwhile, countries exhibiting low CD prevalence included, among others, Estonia (138, 139), and Russia (123) (Table 4). The quite low prevalence rate observed for Denmark, even after its increase over the years (128), indicates that CD awareness is low among healthcare professionals and that serum autoantibody case-finding screening in the primary care field is not often performed.…”
Section: Incidence Rates and Prevalencementioning
confidence: 99%